A Review and Update on the Biochemical Basis of Conscious Breathing (Pranayama) - Carlos Aulesa; Sunil Panchal (Journal of Alternative Medicine and Mind Body Practices, 2026)
Breathing has long been recognised as a vital process in Eastern traditions such as YOGA and Ayurvedic medicine, where Pranayama is regarded as a transformative practice that harmonises body and mind. While the East developed sophisticated systems of breath regulation for health and self-awareness, the West largely overlooked their significance until the late 19th and early 20th centuries. A group of pioneering physicians, sometimes referred to as
Keywords: Pranayama